#TITLE_ALTERNATIVE# - SANTURIMA (NIM: 20212010) ; Pembimbing Wahyu Srigutomo, Ph.D., SESRI
2D forward modeling of gravity anomaly using Abdeslem formulations (2003). Assumed density contras variance depends on depth polynomial. This modeling scheme, depth variable substitution in horizontal distance. Abdeslem formulation used for integrating depth variable, so that simply in singular variable is in distance. Gauss Legendre Quadrature method can integrate results from Abdeslem formulation. Forward modeling generate synthetic data, validated with inversion Levenberg Marquardt. Synthetic data applied to determine the model basin beneath he surface by Fourier approach